Heterogeneous skill distribution and college major: Evidence from PIAAC - Kan Yao (Journal of Applied Economics, 2019)
A large literature documents the uneven distribution of labor market outcomes across majors. Students in STEM (science, technology, engineering, and mathematics) can earn more than their peers. This earnings gap can be attributed not only to the differential educational resources investment but also to heterogeneous distribution of initial cognitive skills across majors. I benefit from the rich data from the Programme for the International Assessment of Adult Competencies to examine this earnings gap in the United Stated and the United Kingdom. Based on my findings, this paper establishes new facts that add to the understanding of how college field premiums are generated. I show that a sizable portion of the return to majors is due to self-selection and up to two-fifths of the field premiums can be explained by basic cognitive skills. Despite the qualitatively similar impacts of numeracy and literacy skills on choosing college field of study, the pricing of numeracy is much higher than literacy in the labor market.
Keywords: 330; cognitive skills; field of study; Wage premiums